2017
DOI: 10.1007/s13197-017-2908-x
|View full text |Cite
|
Sign up to set email alerts
|

A rapid and sensitive evaluation of nitrite content in Saudi Arabian processed meat and poultry using a novel ultra performance liquid chromatography–mass spectrometry method

Abstract: Quantitative assessment of nitrite (NO) anion was performed using a newly developed high throughput ultra performance liquid chromatography-mass spectrometric (UPLC-MS) method. The nitrite determination with the proposed method using micellar mobile phase was unknown. Selected ion reaction mode using negative electrospray ionization was adopted for the identification and quantitative analysis of nitrite. The chromatographic separation was performed using BEH C-18 column and a micellar mobile phase consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Some studies utilised HPLC in method development followed by LC-MS for compound identification. HPLC and LC-MS were selected in forced degradation impurities profiling due to its high precision, accuracy, specificity, selectivity, resolution and capacity ( Marin and Barbas, 2004 ; Ramesh et al., 2014 ; Ramisetti and Kuntamukkala, 2014 ; Bhardwaj and Singh, 2008 ; Siddiqui et al., 2014 , 2018 ; Wabaidur et al., 2013 , 2015 ; Hakami et al., 2020 ). High temperatures and gases source were reported to result in higher sensitivity due to the ionic evaporation ( Khan et al., 2016 , 2020 ; Wabaidur et al., 2016 ).…”
Section: Combination Of Hyphenated Chromatographic and Spectroscopic mentioning
confidence: 99%
“…Some studies utilised HPLC in method development followed by LC-MS for compound identification. HPLC and LC-MS were selected in forced degradation impurities profiling due to its high precision, accuracy, specificity, selectivity, resolution and capacity ( Marin and Barbas, 2004 ; Ramesh et al., 2014 ; Ramisetti and Kuntamukkala, 2014 ; Bhardwaj and Singh, 2008 ; Siddiqui et al., 2014 , 2018 ; Wabaidur et al., 2013 , 2015 ; Hakami et al., 2020 ). High temperatures and gases source were reported to result in higher sensitivity due to the ionic evaporation ( Khan et al., 2016 , 2020 ; Wabaidur et al., 2016 ).…”
Section: Combination Of Hyphenated Chromatographic and Spectroscopic mentioning
confidence: 99%
“…In some kinds of raw food, the presence of nitrite reduces the growth and multiplication of bacteria such as Staphylococcus aureus, E. coli, and Listeria monocytogenes, while the presence of nitrite has no effect on the growth and survival of other lactic acid bacteria strains [2,3]. Numerous studies have shown that nitrite may contaminate food when it is created by an organism that converts nitrate to nitrite or when it is added to food as an additive [4]. In comparison to nitrate, the content of nitrite in groundwater or surface water is usually minimal [5].…”
Section: Introductionmentioning
confidence: 99%